Design and Prototype of a Local Relay Fault Detection System for Three Phase Power Lines. - Lutaama, Samuel (Kabale University, 2025)
This report presented the design and development of a microcontroller-based fault detection and protection system aimed at enhancing the efficiency and reliability of over-current protection mechanisms. The research provides an overview of fault detection systems, highlighting the limitations of current protection systems, which are often expensive and make it difficult to build a reliable network. The project's objective is to create a more accurate, real-time fault detection system. A review of existing systems, including relay-based and microcontroller-based solutions, reveals challenges such as high costs and scalability. The methodology covers system architecture, fault detection algorithms, and the prototype development process, which integrates sensors and a user interface for monitoring. Results show that the system functions effectively, with accurate sensor readings and a responsive user interface, though certain design limitations exist. Safety considerations and current limitations are discussed, along with opportunities for future improvements and expansion. The system holds potential for further enhancement to improve fault detection accuracy and overall system responsiveness